Severe morbidity with sublingual misoprostol in a post-partum patient: a case report - Verma, Sunita; Makkar, Binni; Singh, Netra; Singh, Poonam; Bansal, Shefali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Misoprostol is highly useful in preventing and treating postpartum hemorrhage. However, it may be associated with side effects like fever, chills and vomiting. Rarely may it cause severe morbidity and even death. We witnessed a case of 30 year old female, who developed postpartum hemorrhage immediately after her delivery. Patient was administered various uterotonics including 800 mcg sublingual misoprostol, with which her PPH was finally controlled. However, she developed hyperthermia, hypotension, tachycardia and fall in saturation of O2, after few hours of misoprostol administration. Patient was managed by strict monitoring in ICU setting and mechanical ventilation. She gradually recovered over a period of 48 hours and was discharged in stable condition. Misoprostol should be carefully used as it has a potential to cause serious adverse effects in pregnant and postpartum phase.